The influence of the Epstein-Barr virus on paraclinical indicators and cytokine levels in children with rotavirus gastroenteritis - Sliepchenko, Marharyta; Olkhovska, Olga (ScienceRise: Medical Science, 2023)
The aim. To identify the influence of the latent form of Epstein-Barr virus infection on the clinical picture, parameters of clinical blood analysis and cytokine response of children with rotavirus gastroenteritis. Materials and methods. 56 children were examined. Of them, 33 children (group 1) had no background infection with herpesviruses, and 23 patients (group 2) suffered from rotavirus gastroenteritis against the background of Epstein-Barr virus (EBV) infection. The patients were comparable in terms of sex, age and disease severity. Differences at p <0.05 were considered statistically significant. Results. The analysis of the obtained data showed that the latent form of EBV infection affects the clinical picture, indicators of clinical blood analysis and the reaction of serum cytokines of children with rotavirus gastroenteritis. Сonclusions. A comparative analysis revealed that a latent form of herpesvirus infection in children with rotavirus gastroenteritis is associated with lower temperature reaction and a lower frequency of vomiting in the acute period of the disease against the background of longer persistence of fever, diarrhoea and catarrhal syndromes. On the part of the investigated laboratory indicators, the presence of EBV infection is characterized by a lower level of haemoglobin (р = 0,013) against a higher content of neutrophils (p = 0.002), eosinophils (p = 0.033) and monocytes (p < 0.001) in the acute period of RVI, and a significantly higher content of eosinophils (p = 0.001) and monocytes (p < 0.001) against the background of a lower level of the relative content of lymphocytes compared to patients of Group 1 in the period of early convalescence. Changes in the cytokine response in children with mixed infection are characterized by a significantly lower concentration of IL-1β at the onset of RVI and a higher content of IL-4 and TNF-α throughout the disease compared to children with mono-RVI